Association between waist circumference and hypertension in children and adolescents with intellectual disabilities. Issue 3 (3rd July 2019) - Wyszyńska, Justyna; Podgórska-Bednarz, Justyna; Dereń, Katarzyna; Mazur, Artur
ABSTRACT: Background: The prevalence of abdominal obesity (AO) is high in individuals with intellectual disability (ID). The aim of this study was to assess the prevalence of hypertension (HPT) in students with ID with different distributions of adipose tissue. Method: Study involved 568 participants with ID. AO was assessed on the basis of waist circumference (WC) measurements. Results: The risk of HPT was more than threefold higher in individuals with AO (OR = 3.38) than in the subjects with normal WC. Correlation between the prevalence of AO and HPT was observed in girls and individuals with mild levels of ID (OR = 6.07 and 7.67 respectively). The prevalence of HPT increases sharply in girls whose WC is greater than or equal to the 90 percentile, and in boys when it exceeds the 75th percentile. Conclusion: An association between WC and HPT was observed in abdominally obese students with ID.